Peduli Lingkungan, Laksanakan Program Jumat Bersih dan Kerja Bakti di Desa Hulawa Kabupaten Pohuwato - Permana, Aang Panji; Uno, Djamal Adi Nugroho; Luly, Diwa Ahmad; Tahaku, Ravit; Lahmuda, Zulsiasana (-, 2024)
The largest village in Buntulia District is Hulawa Village with an area of 39,512.21 km2 or around 90.95 percent of the total area of the sub-district. Hulawa Village has a rich and diverse history. Historically, the development of Hulawa Village was also influenced by the political and social dynamics in Gorontalo. The purpose of the environmental service activities carried out by KKN MBKM is to explain the implementation of the KKN community service program in Hulawa Village. The service program in question includes two environmental care programs, namely the clean Friday program and community service. To achieve these goals in implementing their activities, students use three stages of implementation procedures consisting of the preparation stage, the implementation stage and the final stage, namely finishing. The results of the implementation of the service from the two environmental care programs in Hulawa Village ran smoothly and successfully with 100% achievement because community involvement was very large. Both programs that were implemented directly provided environmental cleanliness benefits.